Highly exposed (001) facets Ni(OH)2 induced formation of nickle phosphide over cadmium sulfide nanorods for efficient photocatalytic hydrogen evolution. (20th March 2020) - Yuan, Xiaojie; Shen, Dongyan; Zhang, Qiao; Yang, Guangxing; Zhang, Bingqing; Li, Yuhang; Zuo, Jianlinag; Peng, Feng
Abstract: An efficient Ni2 P–CdS photocatalyst for photocatalytic hydrogen evolution was synthesized by phosphorizing β-Ni(OH)2 nanosheet with exposed (001) facets on CdS nanorods. The obtained Ni2 P–CdS composite displays an outstanding and stable photocatalytic hydrogen generation rate of 68.47 mmol g −1  h −1 in 10 vol% lactic acid under visible light irradiation, more than 17 times higher than that for pure CdS nanorods. The transient photocurrent response, EIS measurement, Mott-Schottky plots, acidic LSV measurement, and PL spectra have proved that Ni2 P loading can significantly improve the separation of photo-excited electron-hole pairs in CdS nanorods and enhance the hydrogen evolution capability for CdS. These improvements are achieved by features of Ni2 P such as the high capability of trapping photo-generated electrons from CdS, lifting the total Fermi level and lowering the hydrogen evolution overpotential of the composite. The results show that β-Ni(OH)2 precursor with a high exposure degree of (001) facet is contributed to the epitaxial formation of (001)-facet-exposed Ni2 P co-catalyst on CdS nanorods, resulting in that the Fermi level and the hydrogen evolution overpotential of the composite can be further lifted and lowered. This study has provided a novel precursor-derived route to fabricate high-performance co-catalysts with highly exposed active facets on CdS nanorods for effective photocatalytic hydrogen evolution. Highlights: Ultrathin β-Ni(OH)2 nanosheet precursor is employed in fabricating Ni2 P on CdS. β-Ni(OH)2 nanosheet with exposed (001) facet facilitate Ni2 P(001) growth on CdS. Hydrogen evolution and charge separation of CdS can be markedly improved by Ni2 P.